Application of a model for implementing reverse logistics in the productive slage - Santos López, Félix Melchor (2010)
Reverse logistic is a recently concept that has been taking more importance, force and interest by enterprises, governments and civil society, because currently we are living a peach of environment conservation and reducing of global warming. In the production phase, this concept is linked with mistakes and leftovers made in the fabrication process whose materials are possible of reuse. Thus, the application of reverse logistic is made by medium and large production enterprises, focused in manufacture, that are looking for reduce of costs and give a responsibility environmental image. In addition, enterprises need automated tools for taking good decisions when appear a mistake in the process production, which is the objective of this research. Finally, this system improves the results in the time, when it adds more data.